2010
DOI: 10.1007/s10653-009-9282-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of lead concentrations in urban surface soils of New Orleans, Louisiana USA

Abstract: Immediately following hurricane Katrina concern was raised over the environmental impact of floodwaters on the city of New Orleans, especially in regard to human health. Several studies were conducted to determine the actual contaminant distribution throughout the city and surrounding wetlands by analyzing soil, sediment, and water for a variety of contaminants including organics, inorganics, and biologics. Preliminary investigations by The Institute of Environmental and Human Health at Texas Tech University c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
(25 reference statements)
1
15
1
Order By: Relevance
“…The average concentration of arsenic was 9 mg/kg (median 6 mg/kg) with a standard deviation of 13 mg/ kg. Based on these data and the known heterogeneity of urban soils (Abel et al 2010), our concentrations appear to be in reasonable agreement with previously reported values.…”
Section: Environ Geochem Healthsupporting
confidence: 92%
See 1 more Smart Citation
“…The average concentration of arsenic was 9 mg/kg (median 6 mg/kg) with a standard deviation of 13 mg/ kg. Based on these data and the known heterogeneity of urban soils (Abel et al 2010), our concentrations appear to be in reasonable agreement with previously reported values.…”
Section: Environ Geochem Healthsupporting
confidence: 92%
“…One month after flood waters had receded contamination of arsenic and vanadium compared to EPA Region 6, background soil levels were found (Su et al 2008). Several groups found elevated lead in soils collected after Katrina (Adams et al 2007;Abel et al 2010;Presley et al 2006;Cobb et al 2006), and some also found cocontaminants such as arsenic and semi-volatile organic compounds (Abel et al 2010;Presley et al 2006;Cobb et al 2006). Rabito et al (2012) discovered that 27 % of samples from households with bare soil contained lead levels exceeding 1200 lg/g after the hurricane; median lead values were significantly higher than those obtained before Hurricane Katrina.…”
Section: Introductionmentioning
confidence: 99%
“…2c), the highest concentrations of Pb occur in the oldest inner city parts of Dublin, with levels declining concentrically with distance from the city centre. Other urban soil Pb studies from around the world have clearly demonstrated a similar pattern (including Abel et al 2010; Haugland et al 2008; and studies cited in Davies 1990). According to our chosen scale breaks, the highest 10 % predictions (predominantly in the city centre) can range from just under 200 mg kg −1 up to highs of over 470 mg kg −1 .…”
Section: Resultsmentioning
confidence: 62%
“…Ireland does not yet have dedicated contaminated land guidance derived exclusively for the Irish environment. For contaminations like Pb, there is no consensus worldwide on the protective threshold for human health in soil (Abel et al 2010), and therefore, it is important to understand local conditions in assessing risks to human health from soil contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Following Hurricane Katrina, hazardous substances such as volatile organic compounds (VOCs), lead, and arsenic were detected in the air, soil, and sediment samples. No health effects have been directly observed in a storm-specific context [54–59]. However, the potential for a toxic release of hazardous substances after a storm exists [5557].…”
Section: Resultsmentioning
confidence: 99%